I am having some problems simplifying the following equation I got as far as

F = (ac' + abd' + acd)' (original equation)

F' = (ac')'(abd')'(acd)'

F' = (a'+c'')(a'+ b'+ d'')(a' + c' + d')

F' = (a' + c)(a' + b' + d)( a' + c' + d') (used Involution / double complement law to deal with the compliments for C and D)

F' = (a' + a'b' + a'd + a'c + b'c + cd)(a'+ c' + d')

From here I am stuck and can't simplify more than that, I am making further research at the moment but I appreciate any help at this stage